Carbon Smart Strategies for Enhanced Food System Resilience Under a Changing Climate - Yeboah, Stephen; Owusu Danquah, Eric; Oteng-Darko, Patricia; Agyeman, Kennedy; Tetteh, Erasmus Narteh (Frontiers in Sustainable Food Systems, 2021)
There is an urgent need to match food production with increasing world population through identification of sustainable land management strategies. However, the struggle to achieve food security should be carried out keeping in mind the soil where the crops are grown and the environment in which the living things survive, especially under rainfed agricultural system. Rainfed agricultural ecosystem is extremely fragile, improving soil fertility and reducing greenhouse gas emission are key factors for developing sustainable agriculture. Moreover, society increasingly expects agriculture to be more sustainable, by decreasing irrigation and mineral fertilizer inputs. Increasing food production sustainably through efficient use of resources will strongly contribute to food security, sustainable agriculture development, and increased climate change resilience. This paper addresses the effects of carbon smart technologies on greenhouse gas emission, soil quality and crop productivity in rainfed agro ecological environment. This paper hypothesized that application of carbon smart technologies could improve soil physical and chemical properties to enhance GHG mitigation and crop production. Carbon smart technologies highlighted in this paper include minimum tillage, crop residue retention, agroforestry, biofuels, integrated nutrient management and land use management systems. This paper review and discusses the work done on carbon smart technologies in different agro-ecological regions so as to understand its impact from the perspectives of the soil, the crop and the environment. The impact of conservation agriculture on greenhouse gas emissions and the underlying mechanism in different agroecological environments have been discussed. A detailed case study and tremendous advancements on the strength of integration of trees and shrub as carbon smart technologies in improving soil and crop productivity is highlighted immensely. The paper concludes with recommendations for encouraging and improving adoption by smallholder farmers to ensure more efficient and sustainable food system. This systematic review will primarily contribute to the achievement of the following Sustainable Development Goals (SDGs), particularly SDG1 (No poverty), SDG2 (Zero hunger), SDG5 (Gender equality) and SDG13 (Climate action).